Incorporating Citizenship Education Framework in Social Studies Teachers’ Education Programme in Sultanate of Oman - Al-Maamari, Saif (International Journal of Humanities and Social Science Research, 2021)
Educational system in Oman is attempting to educate Omani students to be "good" citizens in an increasingly globalized society. However, a few studies that have been conducted until now in Oman revealed a gap between the intentions of the educational policy of teaching citizenship education in the schools and the actual practices of teacher education preparation programs. Therefore, any endeavor to develop citizenship in Oman schools will not achieve its goals without taking teacher education into account both pre-service and in-service. Accordingly, the present study aims to propose a framework for developing citizenship education in the initial teacher education in Oman. This descriptive study highlighted the gap between the policy and practice in social studies teacher education. The international literature reveals that student teachers feel insufficiently prepared to develop citizenship and Omani student teachers are not exceptional. Thus, the present study proposed a framework to incorporate citizenship education in the current teachers' preparation programs. Furthermore, the study reveals the inadequate presence of the topic of citizenship in teacher education. Therefore, teachers' understanding of citizenship becomes shallow, which undoubtedly leads to superficial learning on the part of the students. Therefore, a framework was proposed to develop citizenship in teacher education. This framework consists of the rationale behind the change, the Layout of the ground for change in teacher education, the mechanisms of the change, and the areas of the change.